2020
DOI: 10.1108/itpd-04-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

Organizational transformation as a determinant of corporate hospitality and its effect on corporate sustainability

Abstract: PurposeThis research was conducted with the aim of examining and explaining the effect of strategic leadership, corporate governance, organizational culture, business infrastructure and corporate alignment as determinants of corporate hospitality; testing and explaining the direct effects of corporate hospitality and corporate sustainability.Design/methodology/approachThis research used a quantitative approach with a survey method. The research population was all subsidiaries, branches and departments in PT Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…The Oldham and Hackman job characteristics model also supports the claim that internal motivation is gained through experienced meaningfulness from task variety and task significance (George & Akinwale, 2020). According to (Nimran, Utami, Cahyana, & Iqbal, 2020), followers at lower levels of the organisation may lack the autonomy to promote innovative processes. This is especially noticeable where tasks and responsibilities are more rigid.…”
Section: Intellectual Stimulation (Is)mentioning
confidence: 80%
“…The Oldham and Hackman job characteristics model also supports the claim that internal motivation is gained through experienced meaningfulness from task variety and task significance (George & Akinwale, 2020). According to (Nimran, Utami, Cahyana, & Iqbal, 2020), followers at lower levels of the organisation may lack the autonomy to promote innovative processes. This is especially noticeable where tasks and responsibilities are more rigid.…”
Section: Intellectual Stimulation (Is)mentioning
confidence: 80%
“…It can be defined as a shift in company strategies and operations toward meeting the demands of businesses and stakeholders while also sustaining, maintaining, and improving human and natural resources that will be required in the future (Searcy, 2011). Corporate sustainability is a corporate strategy that focuses on the ethical, social, environmental, cultural, and economic components of doing business (Utami et al, 2020). Corporate sustainability has been described as an organization's strategic and profit-driven response to environmental and social challenges (Calabrese et al, 2019).…”
Section: Sustainabilitymentioning
confidence: 99%
“…Similarly, the importance of sustainability at the corporate level has grown considerably, especially since the majority of industrialized and developing nations embraced sustainable development goals (Du et al, 2022;Zahid et al, 2021). Several studies have identified the impact of sustainability on open innovation (Minutolo et al, 2019;Searcy, 2011;Zhang et al, 2019), with Utami et al (2020) showing that low sustainability negatively affects open innovation. However, these studies did not provide a full understanding by integrating crisis management factors (crisis management, decision-making, risk-taking), sustainability, and open innovation.…”
Section: Introductionmentioning
confidence: 99%
“…The third and final contribution of this study is to investigate how changes in political environment may affect political benefits or costs. Contrary to Utami (2020), this paper explores the effects of political connections on firm performance during the period marked by stable (prerevolution) and unstable (post-revolution) political environment. Previous studies on Tunisian connected firms' performance are interested in either post-revolution period (Bencheikh & Taktak, 2017;Maaloul et al, 2018, Riahi and or the pre-revolution period (Lassoued and Attia, 2014).…”
Section: Political Connections and Firm Performancementioning
confidence: 99%
“…Hence, the following question is raised: does politicians use RPTs to maximize self-serving interests at the expense of other shareholders or to provide benefits to firms through a simplified negotiation process, lower transaction costs and the facilitation of contracts? This issue was addressed in the study of Utami (2020), using Indonesian context. His study advances that the relationship between accounting performance and political connections is more pronounced with greater RPTs.…”
Section: Introductionmentioning
confidence: 99%